2015
DOI: 10.1016/j.semcancer.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the IRE1α–XBP1 branch of the unfolded protein response in human diseases

Abstract: Accumulation of unfolded or misfolded proteins in the endoplasmic reticulum (ER) leads to ER stress, which is characteristic of cells with high level of secretory activity and implicated in a variety of disease conditions. In response to ER stress, the cell elicits an adaptive process called the Unfolded Protein Response (UPR) to support cellular homeostasis and survival. However, prolonged and unsolvable ER stress also induces apoptosis. As the most conserved signaling branch of the UPR, the IRE1α-XBP1 pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(121 citation statements)
references
References 83 publications
3
118
0
Order By: Relevance
“…This indicates that these drugs that have been developed as cancer therapeutics 41 could be positioned to modulate ER-stress responses in human diseases characterized by epigenetic deregulation of the IRE1/XBP1 pathway 55 . Because IRE1 plays a role in tumorigenesis 33,54,56 , it would be important to interrogate how these drugs affect ER-stress responses and what consequences this may have on tumor progression in treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that these drugs that have been developed as cancer therapeutics 41 could be positioned to modulate ER-stress responses in human diseases characterized by epigenetic deregulation of the IRE1/XBP1 pathway 55 . Because IRE1 plays a role in tumorigenesis 33,54,56 , it would be important to interrogate how these drugs affect ER-stress responses and what consequences this may have on tumor progression in treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, IRE1 forms a functional multimer with both serine/threonine kinase and endoribonuclease (RNase) activities in its cytoplasmic domain (16). The RNase domain in IRE1 mediates the cleavage of 26-nucleotide intron from the mRNA encoding X-box binding protein 1 (XBP1) and, with coordinated intervention from the catalytic subunit of the transfer RNA-splicing ligase complex (RTCB), generates a spliced transcript that is translated into an active transcription factor named XBP1s (17). In addition, IRE1 participates in the degradation of various mRNAs and microRNAs (miRNAs) in a process called regulated IRE1-dependent decay (RIDD) (18).…”
Section: Er Proteostasis and Stress Signaling-generalitiesmentioning
confidence: 99%
“…Over the past decade, a growing number of studies have reported that Xbp1s is involved in a wide range of pathophysiological processes, namely, protein folding, glycosylation, ER-associated degradation, autophagy, lipid biogenesis and insulin secretion. 8,9 Of particular note, accumulating evidence suggests that Xbp1s exerts potential regulator effects in cardiovascular diseases, including atherosclerosis, myocardial ischemia/reperfusion injury, and cardiac hypertrophy. 8,10 But so far, the precise functions of Xbp1s in cardiomyocyte hypertrophy are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%